IDENTIFIKASI FAKTOR PENGGUNAAN MEDIA SOSIAL TERHADAP EFEKTIVITAS PENGGUNAAN SHOPEEFOOD DALAM MENINGKATKAN KINERJA USAHA - Utami, Risma; Ardiansah, Irfan (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study aims to identify the factors of using social media on the effectiveness of using ShopeeFood in improving business performance in MSME actors in the field of Food & Beverage in Limo District. This research is a quantitative descriptive research in which the independent variable is the social media adoption variable with the factors of suitability, cost-effectiveness, trust, and interactivity that affect the dependent variable, namely increasing business performance. The data collection method was carried out by distributing questionnaires in the form of a Google form. The data analysis used was multiple linear regression analysis using the SPSS application. The results of the study show that the variables of suitability, cost-effectiveness, trust, and interactivity partially have a significant influence on the Effectiveness of Using the ShopeeFood Application in improving business performance. Then the variable suitability factor, cost-effectiveness, trust factor, and interactivity factor can explain the variation in the increase/decrease in the Effectiveness of Using the ShopeeFood Application in increasing business performance by 79.1%. While the remaining 20.9% is explained by other variables not included in the research model.